(untitled) (Journal of Computational Mathematics, 2004)
In this paper, we consider an inverse scattering problem for an obstacle D ⊂ R^2 with Robin boundary condition. By applying the point source, we give a regularizing method to recover the scattered field from the far-field pattern. Numerical implementations are also presented.